Significance of Lighthing Design - Mr. Huzaifa; Dr. Deepti Pande Rana* (International Journal of Rural and Regional Development, 2024)
Lightning design plays a pivotal role in both architectural and interior design, impacting aesthetics, functionality, and psychological well-being. This research investigates the multifaceted influence of lighting on human emotions, cognitive functions, and overall mental well-being within built environments. Moreover, it explores the visual comfort aspects of lighting design, emphasizing its significance in minimizing glare, shadows, and eye strain to optimize occupant satisfaction. Through a series of case studies, this study exemplifies the application of lighting design principles across various settings. The retail environment case study highlights lighting & dynamic role in shaping customer behavior and enhancing the shopping experience. In the hospitality venue case study, the welcoming ambiance achieved through strategic lighting design is examined from both staff and guest perspectives. Additionally, the residential setting case study demonstrates the adaptability of lighting design to diverse preferences, integrating modern technologies such as smart lighting systems. Furthermore, this research introduces the hanging Cuboidal study lamp as a novel lightning design concept. This innovative lamp not only adds to the aesthetic appeal of interior spaces but also offers functional benefits such as adjustable brightness levels and reduced eye strain during study or work sessions. By scrutinizing the interplay between lighting design and human psychology, this study contributes to a deeper understanding of how lighting influences occupants & experiences and well-being within built environments. It underscores the importance of thoughtful lighting design in creating environments that are visually appealing, comfortable, and conducive to positive psychological states.
Keywords: Aesthetics; Case Studies; Cognitive Functions; Customer Behavior; Eye Strain; Glare; Hanging Cubidol Study Lamp; Hospitality Venue; Human Emotions; Lighting Design; Mental well-being; Occupant Satisfaction; Residential Setting; Retail Environment; Shadows; Shopping Experience; Smart Lighting Systems; Visual comfort; Welcoming Ambiance; adaptability; psychology